2016
DOI: 10.1093/ijnp/pyw003
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine Increases BDNF Serum Levels in Depressed Patients in Correlation with the Improvement of Depressive Symptoms

Abstract: Background:Agomelatine modulates brain-derived neurotrophic factor expression via its interaction with melatonergic and serotonergic receptors and has shown promising results in terms of brain-derived neurotrophic factor increase in animal models.Methods:Twenty-seven patients were started on agomelatine (25mg/d). Venous blood was collected and brain-derived neurotrophic factor serum levels were measured at baseline and after 2 and 8 weeks along with a clinical assessment, including Hamilton Depression Rating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 25 publications
2
42
0
2
Order By: Relevance
“…The efficacy of available antidepressants in anhedonia has been poorly evaluated in the past, even though anhedonia is considered, together with depressed mood, as one of the two symptoms of depression essentials for the diagnosis of the disease (DSM IV, 5). Some psychotropic drugs, also outside the class of antidepressants, have some good potentiality for this core dimension (Jaehne, Corrigan, Toben, Jawahar, & Baune, ; Martinotti, Pettorruso, et al, ; Lally et al, ), but data are still insufficient to draw any conclusion. Even if the results of agomelatine in this important symptom deserve to be confirmed in larger real‐life studies, they offer a very important property to this novel antidepressant that can have an impact in the management of depressed patients especially while considering quality of life and remission.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of available antidepressants in anhedonia has been poorly evaluated in the past, even though anhedonia is considered, together with depressed mood, as one of the two symptoms of depression essentials for the diagnosis of the disease (DSM IV, 5). Some psychotropic drugs, also outside the class of antidepressants, have some good potentiality for this core dimension (Jaehne, Corrigan, Toben, Jawahar, & Baune, ; Martinotti, Pettorruso, et al, ; Lally et al, ), but data are still insufficient to draw any conclusion. Even if the results of agomelatine in this important symptom deserve to be confirmed in larger real‐life studies, they offer a very important property to this novel antidepressant that can have an impact in the management of depressed patients especially while considering quality of life and remission.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review 50 analyzed the possible effect of agomelatine. Its action appears to be mediated mainly through neurotrophins elevation, 51 but further studies are required to prove its efficacy in reducing anhedonic symptoms. 50 Preliminary studies on rats showed that while fluoxetine did not show any antianhedonic properties, imipramine did, but only on a subgroup.…”
Section: Anhedonia and Pharmacological Treatments: Outcome Measure mentioning
confidence: 99%
“…Anhedonia, as transnosographic symptom, has a good potential in dissecting the population involved in neuromodulation trials, in particular it could be used as an outcome predic- 65,66 In fact, the occurrence of anhedonic symptoms would detect possible response predictors to neuromodulation treatment. 51 As discussed, anhedonia has a relevant impact on patients' quality of life. It worsens the rate of suicidal ideation in different samples [67][68][69][70][71] and determines poor social functioning 72 and higher and prolonged hospitalization.…”
Section: Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral levels of BDNF in serum are much higher than in plasma [7]. A considerable number of studies, at both the preclinical and clinical levels, have examined the relationship between BDNF and mental disorders, not just psychotic disorders but depression [8,9], anxiety disorder [8], post-traumatic stress disorder (PTSD) [10], and Alzheimer’s disease [11]. A recent meta-analysis demonstrated that peripheral levels of serum and plasma BDNF were moderately decreased in schizophrenia compared with controls [12].…”
Section: Introductionmentioning
confidence: 99%